Connecting Neuroinflammation and Neurodegeneration in Multiple Sclerosis: Are Oligodendrocyte Precursor Cells a Nexus of Disease? - Psenicka, Morgan W.; Smith, Brandon C.; Tinkey, Rachel A.; Williams, Jessica L. (Frontiers in Cellular Neuroscience, 2021)
The pathology in neurodegenerative diseases is often accompanied by inflammation. It is well known that many cells within the central nervous system (CNS) also contribute to ongoing neuroinflammation, which can promote neurodegeneration. Multiple sclerosis (MS) is both an inflammatory and neurodegenerative disease in which there is a complex interplay between resident CNS cells to mediate myelin and axonal damage, and this communication network can vary depending on the subtype and chronicity of disease. Oligodendrocytes, the myelinating cell of the CNS, and their precursors, oligodendrocyte precursor cells (OPCs), are often thought of as the targets of autoimmune pathology during MS and in several animal models of MS; however, there is emerging evidence that OPCs actively contribute to inflammation that directly and indirectly contributes to neurodegeneration. Here we discuss several contributors to MS disease progression starting with lesion pathology and murine models amenable to studying particular aspects of disease. We then review how OPCs themselves can play an active role in promoting neuroinflammation and neurodegeneration, and how other resident CNS cells including microglia, astrocytes, and neurons can impact OPC function. Further, we outline the very complex and pleiotropic role(s) of several inflammatory cytokines and other secreted factors classically described as solely deleterious during MS and its animal models, but in fact, have many neuroprotective functions and promote a return to homeostasis, in part via modulation of OPC function. Finally, since MS affects patients from the onset of disease through their lifespan, we discuss the impact of aging on OPC function and CNS recovery. It is becoming clear that OPCs are not simply a bystander during MS progression and uncovering the active roles they play during different stages of disease will help uncover potential new avenues for therapeutic intervention.